2012
DOI: 10.1088/1475-7516/2012/11/027
|View full text |Cite
|
Sign up to set email alerts
|

Quantum corrections to inflaton and curvaton dynamics

Abstract: We compute the fully renormalized one-loop effective action for two interacting and self-interacting scalar fields in FRW space-time. We then derive and solve the quantum corrected equations of motion both for fields that dominate the energy density (such as an inflaton) and fields that do not (such as a subdominant curvaton). In particular, we introduce quantum corrected Friedmann equations that determine the evolution of the scale factor. We find that in general, gravitational corrections are negligible for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 80 publications
(158 reference statements)
0
32
2
Order By: Relevance
“…Therefore, in the minimally coupled case ξ = 0 we recovered the classical relation (2.45) between the time-derivatives of the mean field and the Hubble rate. For comparison, in [20] it was found that expanding up to four gradients around Minkowski space, the corrections to the Friedmann equations involve kinetic terms, and the new contributions in energy density and pressure are no longer the same. Also in the present case, however, the quantum correction to the potential force in the field equation does not follow from simple variation from the potential-like quantum contribution in the Friedmann equation, which prevents from using a full analogy with the classical slow-roll formalism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in the minimally coupled case ξ = 0 we recovered the classical relation (2.45) between the time-derivatives of the mean field and the Hubble rate. For comparison, in [20] it was found that expanding up to four gradients around Minkowski space, the corrections to the Friedmann equations involve kinetic terms, and the new contributions in energy density and pressure are no longer the same. Also in the present case, however, the quantum correction to the potential force in the field equation does not follow from simple variation from the potential-like quantum contribution in the Friedmann equation, which prevents from using a full analogy with the classical slow-roll formalism.…”
Section: Discussionmentioning
confidence: 99%
“…These are typically based on a gradient expansion around the Minkowski vacuum, either through adiabatic regularisation [12][13][14][15][16] or at the level of the action using the Schwinger-deWitt expansion [17][18][19][20] for the 1PI effective action. In contrast to the 1PI expansion, in the 2-particle-irreducible (2PI) expansion one uses the dressed propagator in the Feynman diagrams.…”
Section: Jhep05(2014)026mentioning
confidence: 99%
See 2 more Smart Citations
“…where we ignored all U V divergent terms, which are regularisation scheme dependent (related and more detailed computations can be found in [54][55][56][57][58][59]). Now we notice a potential subtlety: if we are interested in a single field case, the inflaton has to be very light compared to the Hubble mass in order to generate density perturbations during inflation.…”
Section: Imaginary Actionmentioning
confidence: 99%